An Analysis of spatial inequalities of Housing quality in middle textures neighboods of zanjan city - Mohsen Ahadnejad; Asghar Teymouri; Mahnaz Vaez livari; Hossein Tahmasebi Moghaddam (تحقیقات کاربردی علوم جغرافیایی)
Housing as one of the basic human needs a significant impact on the health and improve the quality of life of individuals. The quality of housing as one of the main foundations of a comprehensive program and a necessary tool for expressing the various dimensions of economic, social, cultural, environmental and physical development of sustainable, has a special place in urban planning. The purpose of this study is to analyze the spatial quality of housing quality in urban neighborhoods in central Zanjan city. The type of research is applied and descriptive-analytic in nature. The information gathering method was used by the library method (set of statistical blocks of 1395 and detailed plan of 1394). Combined methods of the Tedim model and the geographic information system are used to analyze the data. The results of the research show that inequalities are found among the middle areas of Zanjan city. In the residential areas, 18.91% of the low-quality housing, including the besim neighborhoods, ghabrestan balla, Vahdat, Khatam, Amadgah, Goljak Abad, 21.80% of the dwellings The relatively low quality of the ashaghi gabristan, the shahada, Meydan enghelab , alley waliasr, Niksazan, 22.71% of the average quality housing, including the district of the Forodgah, Rajaee Town, Amjadiyeh, Najaem, Qadas, Fateh, 17.43% of the relatively high quality housing Which includes eastern Ansariyah, Vahidieh, Shoghi, 17  Shahrivar, shahada masged, Goniyeh, Ja'fariyah and ultimately Lots of Azadi, Ansarieh, Etemadieh, Black Alley, North Saadi 19.15% of the houses are of high quality.